Papain Loaded Poly(ε-Caprolactone) Nanoparticles: In-silico and In-Vitro Studies - Budama-Kilinc, Yasemin; Cakir-Koc, Rabia; Kecel-Gunduz, Serda; Zorlu, Tolga; Kokcu, Yagmur; Bicak, Bilge; Karavelioglu, Zeynep; Ozel, Aysen E. (SPRINGER/PLENUM PUBLISHERS, 2018)
Papain is a protease enzyme with therapeutic properties that are very valuable for medical applications. Poly(epsilon-caprolactone) (PCL) is an ideal polymeric carrier for controlled drug delivery systems due to its low biodegradability and its high biocompatibility. In this study, the three-dimensional structure and action mechanism of papain were investigated by in vitro and in silico experiments using molecular dynamics (MD) and molecular docking methods to elucidate biological functions. The results showed that the size of papain-loaded PCL nanoparticles (NPs) and the polydispersity index (PDI) of the NPs were 242.9 nm and 0.074, respectively. The encapsulation efficiency and loading efficiency were 80.4 and 27.2%, respectively. Human embryonic kidney cells (HEK-293) were used for determining the cytotoxicity of papain-loaded PCL and PCL nanoparticles. The in vitro cell culture showed that nanoparticles are not toxic at low concentrations, while toxicity slightly increases at high concentrations. In silico studies, which were carried out with MD simulations and ADME analysis showed that the strong hydrogen bonds between the ligand and the papain provide stability and indicate the regions in which the interactions occur.
Keywords: Papain; Enzyme; Fluorescence; Imaging; PCL; HEK-293; Molecular docking; Molecular dynamic; TRANSFORM INFRARED-SPECTROSCOPY; TRANSDERMAL DRUG-DELIVERY; MOLECULAR-DYNAMICS; TRICHOMONAS-VAGINALIS; SECONDARY STRUCTURE; ACCURATE DOCKING; GENOME SEQUENCE; PROTEIN; INHIBITORS; MODEL; Biochemistry & Molecular Biology; Chemistry